SPEAKING ASSESSMENT: IMPACT OF TRAINING SESSIONS - Mariana Burak (World Science, 2018)
The article focuses on the problem of examiner’s objectivity in rating Speaking proficiency in a foreign language at standardized high-stakes tests. Since there are different factors which may impact the assessment reliability, special training sessions are widely usedby different testing centers. They are expected to eliminate examiners’ subjectivity and lead to interrater agreement and intrarater consistency. The research described in the article was aimed at finding empirical evidence of the efficiency of such sessions. The outcomes of the study proved the sessions to be efficient in terms of rating accuracy of the examiners.